Analisis Rasio Terhadap Laporan Keuangan Pada PT Indofood Sukses Makmur Tbk: Ratio Analysis of Financial Reports at PT Indofood Sukses Makmur Tbk - Kartika, Amelia; Amidana Hikmah, Amalia; Kurnia Damayanti, Amalia; Ainun Najib, M. Thoha (Universitas Bojonegoro, 2024)
Analysis of financial performance with financial ratios of PT. Indofood Sukses Makmur TBK, can be done through financial ratio analysis. The aim of this research is to analyze the performance of PT. Indofood during the 2022-2023 period uses financial ratios. The research results show that in terms of liquidity, the company's ability to fulfill its short-term obligations is quite good. The liquidity ratio, the company's ability to settle short-term obligations has been improved and increased from 2022-2023. Solvency ratios, the situation is less favorable because many ratios have decreased. This could make it difficult for the company to obtain additional loans in the future. Activity ratio, the activity ratio shows the company's efficiency in using assets, which is estimated to be quite good because it has increased. The profitability ratio, performance of PT Indofood Sukses Makmur Tbk is relatively good. Gross profit and net profit will increase significantly from 2022 to 2023